Keefektifan Perangkat Pembelajaran Matematika Berbasis Discovery Learning pada Kelas X SMA - Utami, Nita Putri (Math Educa Journal, 2017)
The learning sets of mathematics used by educators greatly determine the achievement of learning objectives. But the fact that the the learning sets of mathematics used in schools have not supported the achievement of conceptual understanding and reasoning ability to the fullest. The purpose of this research is to produce the learning sets of mathematics based on discovery learning mathematics on equation material and linear inequality that is valid, practical, and effective. This research is a development research using the Plomp development model consisting of initial investigation phase, prototype development or prototype phase, and assessment phase. The effectiveness data is obtained from the cognitive competence test sheet of the learner, observation sheet of students' affective competence and observation sheet of psychomotor competence of the learner. The results showed that the learning sets of mathematics developed were valid, practical and effective. Learning outcomes of learners on cognitive, affective, and psychomotor competencies are effective. In this journal only discussed the effectiveness of learning tools of mathematics.Keywords: Discovery learning, the effectiveness of mathematics  learning  sets based on discovery learning